"Because of english-language television channels": the accidental impact of screen time on children's language acquisition - Nuary, Muhammad Guruh; Rabbani, Adinda Zakiah; Elvina, Nadira; Amelia, Siti; Nurjaman, Iman; Raniyah, Qaulan (Al-Athfaal: Jurnal Ilmiah Pendidikan Anak Usia Dini, 2024)
Background: In the 21st century, the use of technology among children has grown rapidly, making screen time an essential aspect of their language development.Aim: This study aims to explore the impact of exposure to English-language cartoons on the language abilities of preschool children, specifically for S, a 5-year-old child.Method: The research method used is qualitative, employing observation and interview techniques involving S's parents and caregivers as subjects. Data were collected through direct observation and in-depth interviews to understand S's parenting patterns and the use of screen time in daily life. This study offers a new perspective by exploring the impact of unintentional exposure to English-language media as an innovative language acquisition strategy, particularly in the context of early childhood in Indonesia, where similar studies are scarce.Results: The research results indicate that although S experiences speech delays, exposure to English-language cartoons through screen time positively contributes to the development of their English language skills. Interventions by the parents, such as bilingual communication and speech therapy, have accelerated the improvement of these language skills.Conclusion: This study concludes that directed media exposure, supported by active parental involvement, can enhance children's language skills despite initial challenges. Thus, the study emphasizes the importance of effective supervision and management of screen time to support optimal language development.